Catchment systems engineering: An holistic approach to catchment management. (17th February 2020) - Hewett, Caspar J. M.; Wilkinson, Mark E.; Jonczyk, Jennine; Quinn, Paul F.
Abstract: Hydrological catchments today are largely the product of human activity. They have been engineered. The negative impacts of some of this engineering such as deforestation and agriculture intensification need to be addressed but the solution is not simply a matter of doing the opposite, for example through afforestation or moving to less‐intensive farming. We propose a catchment systems engineering (CSE) approach that utilizes and expands on existing catchment‐based approaches, combining interventions that work with or mimic natural processes with traditional "hard" engineering to provide a practical route to improved catchment function. The approach is predicated on the need to take an holistic view of catchments and to make proactive interventions that provide and enhance multiple ecosystem services. CSE seeks to address problems that are international in scope, recognizing the need to understand better how hydrological processes have changed due to human activity and how those changes influence frequency, duration, and severity of environmental problems such as floods, droughts, and poor water quality. The emphasis is placed on how we can act to engineer catchment systems to a safer functionally appropriate level utilizing measures such as nature‐based solutions alongside traditional engineering structures. CSE is the means to provide multiple ecosystem services while recognizing trade‐offs between reducing flood and drought risk directly, improving water quality and creating healthy habitats for wildlife. By targeting local hydrological flow pathways in defined spatial and temporal windows (e.g., during rainfall events at key locations such as riparian zones), CSE can deliver holistic water resource management now. This article is categorized under: Engineering Water > Sustainable Engineering of Water Engineering Water > Planning Water Science of Water > Water Extremes Water and Life > Conservation, Management, and Awareness Abstract : Catchment systems engineering: Integrated holistic catchment management using nature‐based solutions alongside traditional engineering structures.